Evaluation of anxiety level and safety of undergraduate students facing the first endodontic treatment (Research, Society and Development, 2022)
The discipline of Endodontics is considered complex due to its high degree of precision. Estimating the student's level of anxiety and safety is important to understand the student's behavior before, during and after the endodontic intervention. Here the study aims to identify, through the application of sampling to students of the Dentistry course at public and private universities nationwide, the level of stress, anxiety and safety of students in the first endodontic care. This is a cross-sectional study with students enrolled in the Dentistry course at Brazilian universities, between the fifth and tenth periods, who experienced the first endodontic treatment. Data collection was generated through the application of a survey via Google Forms with objective and discursive questions. The results were organized in a database and then solid statistical analyses were performed. A total of 206 scholars participated in this study. When analyzing the results, the participating students showed concern before and during endodontic care, they felt unqualified to perform the treatment, with surgical access being the treatment stage in which the student exposed more limited confidence, and the most used instrumentation procedure was the manual with type K files. According to the previously mentioned data, the lack of clinical experience associated with the complexity of treating the root canal system makes pupils vulnerable to fluctuations in their level of anxiety.